Validation of a streamlined RT-qPCR method for body fluid identification. Issue 1 (December 2019) - Moore, David; Thomson, Jim; Clayton, Tim; Kennedy, Finlay; Beaumont, Dan
Abstract: Forensic DNA STR profiling provides information on the sub-source of DNA samples. However, other source information such as the type of body fluid from which a DNA profile is derived is required to better attribute a matching DNA profile to an individual and to provide activity level evidence. A range of biological molecules such as protein, mRNA and miRNA have been previously used for body fluid identification (BFID). However, many of the published options are complex and require multiple profiling pathways or multiple replicates to obtain interpretable data. We have developed a simplified workflow to deliver an RT-qPCR based system for identification of body fluids using mRNA. The process uses a modified DNA extraction protocol to optimise co-extraction of mRNA and DNA into the same sample eluate, avoiding the requirement for a specialised extraction protocol for mRNA. To simplify the subsequent analysis, we focus on binary tests for two body fluids only, which reflect common questions relevant to different casework scenarios, for example "Does this sample contain saliva or vaginal fluid?" This approach enables the development of smaller, simpler multiplexes using highly specific one-step RT-qPCR assays, designed not to be affected by the presence of genomic DNA. These RT-qPCR multiplexes provide a large dynamic range limiting the number of replicate amplifications required. Here we detail the validation of this streamlined BFID system for identification of saliva and vaginal fluid samples which are commonly encountered in investigations of sexual offences. The study included an assessment on a wide range of sample types obtained from consenting volunteers following sexual activity, providing a robust data set demonstrating the performance of the system.